Akad Dalam Sepakat: Akuntansi Bagi Hasil Nelayan Desa Campurejo - Mohammad Ilham Galang Pratama; Tumirin Tumirin (Jurnal Mutiara Ilmu Akuntansi, 2025)
The purpose of this study is to determine the implementation of profit-sharing agreements among fishermen in Campurejo Village. Profit-sharing among fishermen is an agreement made by two or more parties with the shared goal of utilizing capital to generate profits. Profit-sharing has been practiced by Indonesian society for a long time, with its implementation usually carried out verbally without clear documentation. Another issue arising from profit-sharing is the limited access to capital sources for the majority of fishermen. This study uses a qualitative approach with an ethnomethodology method, and data collection techniques include documentation, interviews, and observation. Interviews were conducted with the "Juragan" fishermen and the "Belah" fishermen. The data analysis technique used in this study is data triangulation. The results of this study show that the profit-sharing practiced by the fishermen community in Campurejo Village follows the mudharabah profit-sharing model, with a profit-sharing ratio of 50% to 50% and 60% to 40%. The profit-sharing practiced by the fishermen community is in accordance with Sharia principles. The researcher recommends documenting transactions in a simple manner to strengthen cooperation with written evidence that will be useful in the future.